Fondasi Iman: Pelayanan Anak-Anak Dalam Perspektif Matius 19:13-15 - Putri Yulia Citra Br. Berutu; Fitri Lyli Septiani Sitompul; Ferdinan Majefat (Jurnal Pendidikan Agama dan Teologi, 2024)
The article focuses on the importance of children's ministry in the perspective of matthew 19:13-15. This article discusses the background to the importance of service in the church, especially service to children as an integral part of church work. This research uses a qualitative descriptive approach by analyzing library sources and describing the results systematically. The discussion of this article covers two main aspects: first, christ-centered children's ministry, which emphasizes the importance of treating children's ministry seriously and appreciating the importance of children in the kingdom of heaven. Second, a discussion of building faith in children's ministry, which includes the responsibility of the church and adults to develop character and build a solid foundation of faith for future generations. The conclusion emphasizes that children's ministry is not just an additional task in the church, but the core of the church's mission that must be prioritized. By paying attention to the strategic role of children's ministry, churches can effectively strengthen the foundations of faith and morality for future generations.